Evaluation of the possibility of detecting microbial contamination of microbial drugs via filtration - S. I. Kuleshova; S. A. Protsak; G. Yu. Romanyuk; S. A. Lisunova; E. N. Semenova (Антибиотики и Химиотерапия, 2022)
The study considered the possibility of using the membrane filtration method as a way of eliminating the antimicrobial effect upon determination of the microbial quality of antimicrobial medicines for oral administration. Azithromycin and amoxicillin powders for suspension, as well as levomycetin (chloramphenicol) and ciprofloxacin tablets were used as examples. The study demonstrated that in some cases the membrane filtration method precluded reliable results. In case of possible contamination of a medicinal product, suspended particles of the active ingredient deposited on a membrane filter may have an inhibitory effect on certain microorganisms due to the spectrum of action of the antimicrobial medicine. A supernatant facilitates filtration upon determination of the microbial quality; however, microorganisms may sediment on suspended particles of the test medicine in the process of suspension separation. The use of the membrane filtration method for the evaluation of the contamination of oral antimicrobial medicinal products should be based on the method validation, taking into account the solubility of the medicine, the composition of excipients, and experimental data on the absence of adhesion of microorganisms on the particles of excipients.